ANALISIS BAHASA SLANG DI MEDIA SOSIAL INSTAGRAM - Siti Pitrianti; Sri Maryani (Jurnal Ilmiah SEMANTIKA, 2023)
This study aims to determine the form of slang (slang) that is widely used by users in posts and comments on Instagram social media. The research method used is descriptive qualitative. Data collection techniques are carried out through observation and documentation. Sources of research data are posts and comments from Instagram user accounts. Data analysis was carried out by observing the content of posts and comments. understand the meaning of the slang used in these posts and comments, and identify patterns in the formation of that language. The findings of the research data are in the form of the formation of slang, namely through phonological, morphological, cognitive semantic, and language variety processes. Keywords: slang, social media, morphology